KEBIJAKAN HUKUM PIDANA DALAM UPAYA MENANGGULANGI TINDAK PIDANA LINGKUNGAN HIDUP (Studi Kasus Penanggulangan Limbah Bahan Berbahaya Dan Beracun Padat Sisa Dari Pmbakaran Batubara Mesin Boiler) - Sri Sufiyati; Munsyarif Abdul Chalim (UNISSULA Semarang, 2017)
In term of tacking environmental crime, this research will discuss about criminal law policy of overcoming the environment crime prevention related to the dumping of Hazardous and Toxic Waste without permission. Based on the Thesis description, the problem that will be in the first examination is the criminal law policy to tackle environmental crime in the current positive law. Second, criminal law policy tackles environmental crime in the future.The purpose of this research is to analyze criminal law policy to tackle environmental crime in positive law today and in the future.The result of the research concludes that the aspect of the imposition of sanctions contained in Law Number 32 Year 2009 on Environmental Protection and Management related to criminal sanctions against perpetrators and business entities proven to dump Hazardous and Toxic Wast is considered inappropriate in an effort to tackle environmental crime. Further related to the Criminal Aspect, it is fitting that criminal sanctions imposed on Hazardous and Toxic Wast dumping action to environmental media without permission are more severe than the current provisions Keywords: Criminal Law Policy, Environmental Crime